Effect of ascorbate oxidase over-expression on ascorbate recycling gene expression in response to agents imposing oxidative stress - Fotopoulos, Vasileios; Sanmartin, Maite; Kanellis, Angelos K. (My University, 2006)
Ascorbate oxidase (AO) is a cell wall-localized enzyme that uses oxygen to catalyse the oxidation of ascorbate (AA) to the unstable radical monodehydroascorbate (MDHA) which rapidly disproportionates to yield dehydroascorbate (DHA) and AA, and thus contributes to the regulation of the AA redox state. Here, it is reported that in vivo lowering of the apoplast AA redox state, through increased AO expression in transgenic tobacco (Nicotiana tabacum L. cv. Xanthi), exerts no effects on the expression levels of genes involved in AA recycling under normal growth conditions, but plants display enhanced sensitivity to various oxidative stress-promoting agents. RNA blot analyses suggest that this response correlates with a general suppression of the plant's antioxidative metabolism as demonstrated by lower expression levels of AA recycling genes. Furthermore, studies using Botrytis cinerea reveal that transgenic plants exhibit increased sensitivity to fungal infection, although the response is not accompanied by a similar suppression of AA recycling gene expression. Our current findings, combined with previous studies which showed the contribution of AO in the regulation of AA redox state, suggest that the reduction in the AA redox state in the leaf apoplast of these transgenic plants results in shifts in their capacity to withstand oxidative stress imposed by agents imposing oxidative stress.
Keywords: Apoplast; Ascorbate oxidase; Biotic stress; Botrytis cinerea; Oxidative stress; Transgenic plants